Research of volt-ampere characteristics of the wire pierce electron gun at electron-beam microprocessing of dielectrics - Bondarenko, Maksym; Antonyuk, Viktor; Kovalenko, Yurii; Rud, Maksym; Haidash, Roman (Lviv Politechnic Publishing House, 2018)
The article considers the basic energy characteristics of a wire Pierce electron-beam gun, which used for microprocessing of dielectric materials in vacuo. The aim of the work is to determine the optimal regimes of electron-beam microprocessing of dielectric materials by studying the volt-ampere characteristics of the wire Pierce electron-beam gun. In the methodical part of the scientific work, a technological experiment with electron-beam microprocessing of dielectric surfaces is proposed, and also identified and studied the operating modes of the Pierce electron-beam gun in depending on their energy characteristics. As a result, the analysis of the obtained results of electron-beam microprocessing of surfaces of dielectric materials makes it possible to increase the reproducibility of the results of such treatment in terms of purity and residual nanorelief by 18–25 %. The comparison of the results of experimental electron-beam microprocessing of dielectrics with the results of their laser processing made it possible to establish a decrease in the residual microroughness of the surface of the optical glass K8 by 17...27 times with electron-beam microprocessing and by 12–14 times with surface laser treatment. Wherein, surface laser processing does not allow to eliminate the undulation of the surface, which is related to the specificity of the interaction of the laser beam with the surface of the optical material, whereas, when processing by the ribbon-shaped electronic stream such undulation does not appear. Conclusions and analyzed data obtained in the article based on the results of experimental studies can be used to optimize the technological regimes of electron-beam microprocessing in the production of micro-optics products, integrated optics, microelectrooptics, nanoelectronics, etc.
Keywords: electron-beam microprocessing; Pierce electron gun; volt-ampere characteristics; micro-optics products; dielectric materials; atomic-force microscopy